IDENTIFIKASI MESOSCALE CONVECTIVE COMPLEX (MCC) DAN DAMPAKNYA TERHADAP CURAH HUJAN DI BENUA MARITIM INDONESIA (BMI) SEPANJANG TAHUN 2018 - Deni Septiadi; Yudhi Nugraha Septiadi (Jurnal Meteorologi dan Geofisika, 2019)
One year observation of Mesoscale Convective Complexes (MCCs) over the Indonesian Maritime Continent (BMI) and its impact to the rainfall are analyzed. This study is focused on the area of BMI where the MCCs formed and then the criteria are identified based on the size, initiate, duration, shape, and the eccentricity.  In term of rainfall, this research also confirm that MCCs  will have an impact to the rainfall distribution around the MCCs area.  The first MCCs was developed on March, 15 and covered 348,410 km2 of the area. The most significant of MCCs was contributed to a 108 mm of rainfall occurs on December, 28 with 11 hours of duration and covered 771,448 km2 of area. The lag-time between rainfall and the mature stage of MCCs could be 1-3 hours.  Furthermore, all initiations of the MCC occurred at night with a duration of between 8-15 hours. Throughout the MCCs event,  top cloud of temperature derived by the Multi-functional Transport Satellite (MTSAT)-IR imagery could reached the temperature < -85 °C. Keywords : MCCs, BMI, rainfall, cloud